HUBUNGAN ANTARA ELECTRONIC WORD OF MOUTH (E-WOM) DENGAN KEPUTUSAN PEMBELIAN PRODUK NYAMBEL RAMPAI GEH MELALUI INSTAGRAM DI KALANGAN GENERASI Z (FOLLOWERS) - Meri Safarwati Putri; Najla Khairunnisa Iswindari (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This research adopts a quantitative approach with a correlational research method. The purpose of this study is to examine Electronic Word of Mouth (e-WOM), consumer purchase decisions of Nyambel Rampai Geh, and the relationship between the two through Instagram among Generation Z. Data collection methods included distributing questionnaires to 100 respondents who are active followers of the Instagram account @sambelrampai_official, documentation to obtain secondary data, and conducting a literature review. Data analysis was conducted using Pearson’s correlation coefficient test with inferential statistics to measure the relationship between variables. The research results show a relationship between e-WOM and purchase decisions, but the relationship is relatively weak. Based on Pearson’s correlation coefficient test, a coefficient value of –0.195 was obtained with a significance level of 0.194. These findings indicate that the existing e-WOM content has not been effective in improving purchase decisions for Nyambel Rampai Geh among Generation Z on Instagram.